Pengaruh Variasi Bentuk Bilah dan Debit Air Terhadap Unjuk Kerja Turbin Kinetis - Muhammad Hasan Basri (Universitas Negeri Malang, 2026)
The growing demand for electrical energy and the limited availability of environmentally friendly renewable energy sources have driven the utilization of hydropower trought kinetic turbines. The study aims to examine the impact of change in blade morphology and waterflow velocity on the efficiency of kinetic turbines. The variations used in this study involved vertical axis kinetic turbines with flat blades, bowl shaped blades, and angeled blades, as well as variations in water flow rate 117 Lpm, 122 Lpm, 127 Lpm, 132 Lpm. This study employed an experimental method, with test parameters including voltage, current, electrical power, and turbine efficiency. The results of the study indicate thet the blade shape and waterflow velocity together have a significant impact on turbine performance. The bowl shaped blades achieved the highest efficiency at 40,07%, the flat blades at 37,86%, and the angled blades at 31,12%.